The Effect of Competitive Small Exercises on the Development of Football Primer Club Players’ Speed Types - Essam, Athear; Nagi, Ahmed (Journal of Physical Education, 2019)
The importance of the research lies in the preparation of small sided games for developing speed types in primer football clubs. The problem of the research lies in weak level of performance thus the importance lies in developing speed types in football teams. The researchers used the experimental method. The subjects were (25) players from Baghdad and Al Shorta clubs for the season 2015 – 2016. The data was collected and treated using SPSS to come up with the conclusion and recommendations.